Creatine kinase in human erythrocytes: a genetic anomaly reveals presence of soluble brain-type isoform - Kay, Laurence; Tokarska-Schlattner, Malgorzata; Bugert, Peter (Blood cells, molecules & diseases, 2017)
For maintaining energy homeostasis, creatine kinase (CK) is present at elevated levels in tissues with high and/or fluctuating energy requirements such as muscle, brain, and epithelia, while there is very few CK, if any, in peripheral blood cells. However, an ectopic expression of brain-type creatine kinase (BCK) has been reported for platelets and leukocytes in an autosomal dominant inherited anomaly named CKBE. Here we investigated CK in erythrocytes of CKBE individuals from eight unrelated families. The data revealed a varying but significant increase of CK activity in CKBE individuals as compared to controls, reaching an almost 800-fold increase in two CKBE individuals which also had increased erythrocyte creatine. Immunoblotting with highly specific antibodies confirmed that the expressed CK isoform is BCK. Cell fractionation evidenced soluble BCK, suggesting cytosolic and not membrane localization of erythrocyte CK as reported earlier. These results are discussed in the context of putative CK energy buffering and transfer functions in red blood cells.
Available online 18 March 2017
Gesehen am 30.07.2018